Lead Menace: A Persistent Issue in Painted Housing Units in Lagos, Nigeria - Folashade, Obidi Olayide (The Asia Journal of Applied Microbiology, 2014)
This study evaluates Pb occurrence in homes in order to assess the toxicity risk in Lagos, Nigeria. Painted wall scrapings were collected from selected locations in Lagos metropolis. The relationship between Pb-based paints applied on family housing units and socio-economic status of residents were compared. Forty eight exterior and interior samples were collected from twelve urban locations and twelve rural locations. The bacterial population density in paint scrapings from rural locations ranged from 1.0 - 2.1 and 0.5 - 1.9 x 105 cfu/g. However, in the urban samples, it ranged from 1.6 - 26.1 and 2.0 – 24.0 x 104 cfu/g for the exterior and interior samples respectively. Atomic absorption spectrophotometry (AAS) showed that in rural samples, Pb concentration ranged from 0.000 – 3.175 and 0.000 – 2.688 ppm while in urban samples, 0.129 – 19.26 and 0.000 – 18.21ppm for exterior and interior samples respectively. Generally, Pb concentration was higher in urban interior and exterior samples than in rural samples. The isolated bacteria were identified using the Analytical Profile Index (API) to be Bacillus megaterium, Enterobacter gergoviae, B. circulans, and B. subtilis from rural samples and Pseudomonas putida, Proteus mirabilis, B. lentus, E. amnigenus, Klebsiella oxycota, Citrobacter youngae and Pantoea sp. from the urban samples respectively.